F and CF3 substituted solution processable oligo para-phenylenevinylene for ambipolar and hole-transporting organic field effect transistors - Chini, Mrinmoy Kumar; Das, Chayanika; Chatterjee, Shyambo (Chemical Physics Letters, 2016)
We have synthesized benzotrifluoromethyl group substituted para-phenylenevinylene oligomer (denoted as PI) and a cooligomer (denoted as PII) by Gilch polymerization route. The ambipolar field-effect transistor (FET) material PI shows hole and electron mobility 1 x 10 (4) cm(2) V (1) s (1) and 2 x 10 (5) cm(2) V (1) s (1) respectively. PII shows only hole mobility as high as 0.05 cm(2) V (1) s (1) as p-type material. This work highlights the progress of hole-transporting as well as ambipolar material for para-phenylenevinylene derivatives. The results are enlightened on the basis of presence of electronegative substituents and structural modification of the oligomer backbone. (C) 2016 Elsevier B.V. All rights reserved.